Aplicação do índice de rendimento operacional global (IROG) em uma linha de produção - (:unkn) unknown (Universidade Federal do Pampa, 2015)
Production systems are tools used everyday in every company from its origins until nowadays. Thanks to these systems, companies are able to produce goods of good quality faster. Workplace management is one of these systems and comes from the Total Productive Maintenance (TPM), which aims to eliminate/reduce wastes associated to the machines, and it also intends to increase productivity and by consequence improve the financial-economical performance of the company. The aim of this paper is to use a tool called IROG (Global Operating Profit Index) which belongs to the MPT range of tools for increasing the operating efficiency of a work station. Consequently, it will be possible to increase the global efficiency of the equipments which belong to the work station analyzed. Hence data collections will be held within the workplace and there will be participation in inspections and maintenance. Through the collected data it will be possible to calculate the IROG of the bottleneck operations, it will be held Pareto diagrams on those machines which are restraining the production, the information will be analyzed and the problem will be revealed, then, it will be possible to fix the problem or at least minimize it. The productive efficiency of lifting ideas will be analyzed through simulations on a software called ProModel.
Keywords: Mechanical Engineering; Machines; Industrial efficiency; Toyota production system; Engenharia mecânica; Máquinas; Sistema Toyota de produção